Risks of Short-termism in Macro-prudential Policy Making: The Case of Household Debt in Korea - Youngil Kim (Korea Development Institute (KDI), 2019)
- Korea's household debt continues to be a major economic risk despite countermeasures, necessitating a thorough overhaul of the current macro-prudential management system. - The debt expanded to 1,514 trillion won in 3Q 2018 from a decade ago (713 trillion won in 2008), considerably exceeding the income growth during the same period. - The rapid increase suggests that past policy measures have been ineffective in achieving a soft landing. - This study adopts a political economy perspective to determine the obstacles to past macroprudential policies, which can be effective tools in terms of credit risk management, and suggests directions for improvement. - It was found that the more fixated policy makers are on the short-term gains in growth and employment, the less likely they are to seek macro-prudential policies for financial stability. - Short election cycles can narrow the horizon of policy decisions, hence policy makers often pursue those with immediate outcomes to earn the public's favor1em1pteven if they entail negative fallouts. - The failure to implement suitable and timely macro-prudential policies will increase the probability of a credit boom-driven crisis and restrict the scope of mid- to long-term economic policies. - To improve the macro-prudential management system, its institutional basis needs to be consolidated to prevent the policy horizon from becoming narrower. - An institutional mechanism should operate the macro-prudential management system in correspondence with the mid- to long-term preference of the national economy. - More practical measures should be considered and adopted which could strengthen public accountability and the operational independence of the macro-prudential management system.
Keywords: 330